Mechanism of regulation of tomato TRN1 gene expression in late infection with tomato leaf curl New Delhi virus (ToLCNDV). (December 2015) - Mandal, Arunava; Sarkar, Deepti; Kundu, Surekha; Kundu, Pallob
Highlights: Leaf curl disease symptom resembles developmental defects. Tomato TORNADO1 ( SlTRN1 ) mRNA level is upregulated in leaf curl virus infected leaves. WRKY16 interacts with W-boxes in SlTRN1 promoter and mediates activation. Activation of SA pathway leads to induction of WRKY16 and subsequently SlTRN1 gene. Altered regulation of SlTRN1 during stress-response may affect severity of symptoms. Abstract: Tomato leaf curl disease caused by geminiviruses is manifested by curling and puckering of leaves and thickening of veins, resembling developmental defects. This is probably due to the long-term altered regulation of expression of development related gene(s). Our results show that in the infected leaves the transcript level of TORNADO1 ( SlTRN1 ), a gene important for cell expansion and vein formation, increased significantly. SlTRN1 is transcribed from two start sites. The preferential usage of one start site governs its expression in viral-stressed plants. To investigate the role of specific promoter elements in mediating differential expression of SlTRN1, we performed SlTRN1 promoter analysis. The promoter-regulatory sequences harbor multiple W-boxes. The SlWRKY16 transcription factor actively interacts with one of the W-boxes. WRKY proteins are commonly induced by salicylic acid (SA), and consequently SA treatment increased transcript level of SlWRKY16 and SlTRN1. Further mutational analyses confirmed the role of W-boxes in mediating SlTRN1 induction during ToLCNDV infection or SA treatment. We postulate that the activation of SA pathway during stress-response in tomato induces WRKY16, which in turn modulates transcription of SlTRN1 gene. This study unravels the mechanism of regulation of a developmental gene during stress-response, which may affect the severity of symptoms.